2020
DOI: 10.1007/s00410-020-1669-0
|View full text |Cite
|
Sign up to set email alerts
|

Magma evolution at La Fossa volcano (Vulcano Island, Italy) in the last 1000 years: evidence from eruptive products and temperature gradient experiments

Abstract: The intense explosive and effusive volcanic activity of the last 1000 years at La Fossa volcano (Vulcano Island, Italy) was characterized by the eruption of magmas ranging in composition from latites to trachytes and rhyolites, as well as K-rich trachytes. Evidence of syn-eruptive mixing among these magmas is frequently observed in the form of magmatic enclaves and bands in lava flows and pyroclastic products. The petrological and volcanological diversity of the erupted materials suggests that complex differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 68 publications
(139 reference statements)
5
44
0
Order By: Relevance
“…The recent (i.e., in the last 1000 years) volcanic sequence of La Fossa volcano on the island of Vulcano, Italy represents a study case suitable to investigate the relationships between a mush-dominated crustal plumbing system and the geochemical variability of the erupted magmas. Volcanic products are in fact characterized by remarkable chemical heterogeneities, either in the form of mingled crystal-rich, latitic-trachytic magmatic enclaves in rhyolitic lavas and pyroclasts, or as mingled and partially mixed lati-trachytic and rhyolitic domains in pyroclasts and lavas [19][20][21][22]. Notably, these features are observed both at the scale of the eruptive sequence and within single eruptive units [19,22] and they have been attributed to mixing processes between intermediate mafic and rhyolitic melts, according to different petrogenetic models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent (i.e., in the last 1000 years) volcanic sequence of La Fossa volcano on the island of Vulcano, Italy represents a study case suitable to investigate the relationships between a mush-dominated crustal plumbing system and the geochemical variability of the erupted magmas. Volcanic products are in fact characterized by remarkable chemical heterogeneities, either in the form of mingled crystal-rich, latitic-trachytic magmatic enclaves in rhyolitic lavas and pyroclasts, or as mingled and partially mixed lati-trachytic and rhyolitic domains in pyroclasts and lavas [19][20][21][22]. Notably, these features are observed both at the scale of the eruptive sequence and within single eruptive units [19,22] and they have been attributed to mixing processes between intermediate mafic and rhyolitic melts, according to different petrogenetic models.…”
Section: Introductionmentioning
confidence: 99%
“…Ref [24,25] proposed instead that the crystal-rich enclaves occurring in the same eruption can be reconciled with the injection of the latitic magma into the more evolved rhyolitic magma. Ref [26], and more recently [21,27], suggested that crystal-rich enclaves occurring in the Pietre Cotte lava are the result of remobilization of crystal-rich cumulates, derived from a crystal mush. Following this latter interpretation, the association between crystal-poor rhyolites and (heterogeneous) crystal-rich enclaves at La Fossa can provide the ultimate evidence of the twofold role of crystal mushes in the origin of differentiated silicic magmas and their eventual segregation to feed volcanic eruptions in small arc systems.…”
Section: Introductionmentioning
confidence: 99%
“…The plumbing system of La Fossa is polybaric, dominated by fractional crystallization, crustal assimilation and magma mixing processes (Costa et al, 2020;De Astis et al, 2013;Peccerillo et al, 2006). These occur in a shoshonitic to latitic magma chamber at about 15 km deep, fed by shoshonitic basaltic magmas, and in shallower and smaller trachytic to rhyolitic reservoirs at 5-2 km deep (Costa et al, 2020;De Astis et al, 2013;Fulignati et al, 2018). Basaltic magmas have been only erupted at about 50 ka.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…t2:3 neglected crustal assimilation processes. The model employs bulk distribution coefficient for Zr, Cu and Pb, calculated for each step of the differentiation process using partition coefficients derived from the literature and the relative proportions of crystallizing phases for Vulcano (Costa et al, 2020; see Supplementary Material S1 for details of the model). The sulfide phase/silicate melt partition coefficients for Pb and Cu were calculated according to Li and Audétat (2015) (Supplementary Material S1).…”
Section: Evolution Of Metals In the Magmasmentioning
confidence: 99%
See 1 more Smart Citation